Preparation and characterization of magnetic nanoparticles embedded in hydrogels for protein purification and metal extraction - Nagireddy, Narayana Reddy; Yallapu, Murali Mohan; Kokkarachedu, Varaprasad; Sakey, Ravindra; Kanikireddy, Vimala; Alias, Joy Pattayil; Konduru, Mohana Raju (Journal of Polymer Research, 2011)
The present work involves the development of hydrogel magnetic nanocomposites for protein purification and heavy metal extraction applications. The magnetic nanoparticles (MNPs) were prepared in situ in poly(acrylamide)-gum acacia (PAM-GA) hydrogels. The formation of magnetic nanoparticles in the hydrogel networks was confirmed by Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). Scanning electron (SEM) microscopy studies revealed the formation of MNPs throughout the hydrogel networks. The average size of MNPs formed in the hydrogel networks was 3-5 nm as determined by transmission electron microscopy (TEM). The thermal properties of the hydrogel magnetic nanocomposites were evaluated by dynamic scanning calorimetry (DSC) and thermogravimetric (TG) analysis. The magnetic properties of the developed hydrogel magnetic nanocomposites were determined by a vibrating sample magnetometer (VSM). The swelling properties of the hydrogel and the hydrogel magnetic nanocomposites were studied in detail. The hydrogel magnetic nanocomposites are utilized for the removal of toxic metal ions such as Co(II), Ni(II), and Cu(II) and for protein purification. The results confirm that the hydrogel magnetic nanocomposites exhibit superior extraction properties to hydrogels.
Keywords: Bioseparation; Hydrogel; magnetic properties; Metal absorption; Nanocomposite